The Lectin LecA Sensitizes the Human Stretch-Activated Channel TREK-1 but Not Piezo1 and Binds Selectively to Cardiac Non-myocytes - Elisa Darkow; Elisa Darkow; Elisa Darkow; Elisa Darkow; Eva A. Rog-Zielinska; Eva A. Rog-Zielinska; Josef Madl; Josef Madl; Annette Brandel; Annette Brandel; Lina Siukstaite; Lina Siukstaite; et al. (Frontiers in Physiology, 2020)
The healthy heart adapts continuously to a complex set of dynamically changing mechanical conditions. The mechanical environment is altered by, and contributes to, multiple cardiac diseases. Mechanical stimuli are detected and transduced by cellular mechano-sensors, including stretch-activated ion channels (SAC). The precise role of SAC in the heart is unclear, in part because there are few SAC-specific pharmacological modulators. That said, most SAC can be activated by inducers of membrane curvature. The lectin LecA is a virulence factor of Pseudomonas aeruginosa and essential for P. aeruginosa-induced membrane curvature, resulting in formation of endocytic structures and bacterial cell invasion. We investigate whether LecA modulates SAC activity. TREK-1 and Piezo1 have been selected, as they are widely expressed in the body, including cardiac tissue, and they are “canonical representatives” for the potassium selective and the cation non-selective SAC families, respectively. Live cell confocal microscopy and electron tomographic imaging were used to follow binding dynamics of LecA, and to track changes in cell morphology and membrane topology in human embryonic kidney (HEK) cells and in giant unilamellar vesicles (GUV). HEK cells were further transfected with human TREK-1 or Piezo1 constructs, and ion channel activity was recorded using the patch-clamp technique. Finally, freshly isolated cardiac cells were used for studies into cell type dependency of LecA binding. LecA (500 nM) binds within seconds to the surface of HEK cells, with highest concentration at cell-cell contact sites. Local membrane invaginations are detected in the presence of LecA, both in the plasma membrane of cells (by 17 min of LecA exposure) as well as in GUV. In HEK cells, LecA sensitizes TREK-1, but not Piezo1, to voltage and mechanical stimulation. In freshly isolated cardiac cells, LecA binds to non-myocytes, but not to ventricular or atrial cardiomyocytes. This cell type specific lack of binding is observed across cardiomyocytes from mouse, rabbit, pig, and human. Our results suggest that LecA may serve as a pharmacological tool to study SAC in a cell type-preferential manner. This could aid tissue-based research into the roles of SAC in cardiac non-myocytes.